Ethnobotanical Study of Rattans on Suku Anak Dalam Community in Bukit Duabelas Nasional Park - Dwi Mairida; Muhadiono Muhadiono; Iwan Hilwan (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Suku Anak Dalam (SAD), a tribal in Bukit Duabelas Nasional Park (TNBD) has knowledge for utilizing rattans. This research attempts to investigate the species of rattans utilized and to analyze the local wisdom of Suku Anak Dalam(SAD) community.The data was collected by doing an interview the informants consisting of temenggung (head of the tribe), jenang (the liaison between the villagers and anak dalam), rattans gatherers, induk (mother) and hand maker. Then, the researcher observed active participation (following the SAD activity in utilizing rattans).The interview was conducted based on the appropriate time with qualitative condition and situation. The result showed 12 (twelve) species of rattan utilized by the SAD community, Calamus ornatus (Blume), Calamus caesius( Blume), Calamus flabellatus (Becc.), Calamus manan(Miq.), Calamus csipionum (Lour.), Calamus javensis(Blume), Calamus axilliaris(Becc.), Calamus sp., Daemonorops geniculata (Griff.) Mart., Daemonorops draco(Willd.) Blume, Daemonorops verticiliaris(Griff.) Mart., and Korthalsiaechinometra(Becc.)The eight species were utilized as ambung, penampilan, and tekalo handicraft. One type for rituals, ropes, clotheslines, dye, durian lempok cakes preservatives (Durio spp.),and the species for the food for pregnant mothers (‘ngidam’), and the three species for medicine. The implication of this research gave a documentation for the government to formulate and to make an authority of TNB forest conservation and to protect the culture of SAD community in the form of rattans inventarization and local wisdom of SAD community in utilizing the species of rattans.How to CiteMairida, D., Muhadiono, M., Hilwan, I. (2016). Etnobotanical Study of Rattans on Suku Anak Dalam Community in Bukit Duabelas Nasional Park. Biosaintifika: Journal of Biology Biology Education, 8(1) 64-70.